Comparing the Clinical Outcome of Transepithelial and Conventional Photorefractive Keratectomy in Correction of Moderate Myopia - Nassiri, Nader; Shahriari , Mansoor; Rezaee Alam , Zahra; Kavousnezhad , Sara; Yadgari, Maryam; Sheibani , Kourosh (Journal of Ophthalmic and Optometric Sciences, 2024)
Purpose: To compare the clinical outcomes of one-step transepithelial photorefractive keratectomy (tPRK) with those of conventional photorefractive keratectomy (PRK) in correction of moderate myopia. Patients and Methods: In this prospective, randomized case-control study consecutive patients with moderate myopia were randomly assigned to undergo either one-step tPRK or conventional PRK using the Schwind Amaris excimer laser system at Vanak Eye Surgery Center, Tehran, Iran, from May to December 2020. Outcome measures included one and three months post-surgical uncorrected visual acuity (UCVA), best corrected visual acuity (BCVA), sphere, cylinder, spherical equivalent (SE), intraocular pressure, haze, and levels of pain and discomfort. Results: One hundred and twenty eyes from 60 consecutive patients were evaluated. No statistically significant differences were observed in mean UCVA, BCVA, or SE at one and three months postoperatively. One month postoperatively, the mean haze was significantly lower in the tPRK group compared to the PRK group (P < 0.001), but this difference was not observed at three months. Patients undergoing tPRK experienced significantly less pain (P = 0.027) and discomfort (P < 0.001) one day postoperatively. No differences between the two groups regarding postoperative intraocular pressure were observed. Conclusion: The findings of the present study suggest that the tPRK method is associated with reduced early postoperative pain and discomfort at day one as well as less corneal haze at one month postoperatively, compared to the conventional PRK method. There were no significant differences between the two methods in terms of postoperative intraocular pressure, UCVA, BCVA, or SE.